A reflection of historical events of the Kazakh khanate formation period in verbal literature (Journal of history, 2019)
Historical events experienced by Kazakh people reflected in verbal literature. Therefore the researchers of Kazakh khanate history couldn’t ignore a heritage of Kazakh literature. Kazakh people are people that developed the history through literature. History and literature of Kazakh people are very close. Rich heritage of people history is saved in folklore.Verbal literature of Kazakh people especially strongly developed in ХІІІ – ХVІІІ c. A verbal poetry was developed for kipshak and other turkic tribes. Poetry of the real masters of artistic word as Sypyra, Kodan taishy, Assan kaigy and Kaztugan (ХІV – ХVІ cc.) were widely known among people and their poems were saved as describing historical reality. Due to the reference of this period to the period of Kazakh khanate formation these compositions include information characterizing public life of that epoch.